2015
DOI: 10.1039/c5sm01413a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic aspects of the adsorption of xyloglucan onto cellulose nanocrystals

Abstract: In this work, the adsorption of a neutral flexible polysaccharide, xyloglucan (XG), onto thin cellulose nanocrystal (CNC) surfaces has been investigated to get more insight into the CNC-XG association. Gold-coated quartz crystals were spin-coated with one layer of CNC, and XG adsorption was monitored in situ using a quartz crystal microbalance with dissipation (QCM-D). The adsorption of XG under flow at different concentrations did not result in the same surface concentration, which evidenced a kinetically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 58 publications
8
65
0
Order By: Relevance
“…The two-step adsorption mechanism of xyloglucan on cellulose was previously proposed by some authors (Pirich et al 2015;Villares et al 2015;Dammak et al 2015). Moreover, Winter et al (Winter et al 2010) showed that the stability of the bacterial cellulose nanocrystal suspension increases above a certain concentration ratio of xyloglucan, which may be due to a change in the dominant molecule conformation on the surface.…”
Section: Adsorption Kineticsmentioning
confidence: 95%
See 1 more Smart Citation
“…The two-step adsorption mechanism of xyloglucan on cellulose was previously proposed by some authors (Pirich et al 2015;Villares et al 2015;Dammak et al 2015). Moreover, Winter et al (Winter et al 2010) showed that the stability of the bacterial cellulose nanocrystal suspension increases above a certain concentration ratio of xyloglucan, which may be due to a change in the dominant molecule conformation on the surface.…”
Section: Adsorption Kineticsmentioning
confidence: 95%
“…These processes are most likely diffusion and reconformation. The analysis of the presented data and findings of Villares et al (2015) allow us to postulate that the fast process (which contributes to 0.243 of the total adsorption kinetics) is a diffusion through a dense cellulose suspension and/or surface diffusion in the adsorbed layer, and the limiting and dominant one (explaining 0.757 of adsorption) is reconformation of molecules in the adsorbed layer. The fast process most likely occurs when the locally surface concentration of xyloglucan (adsorption) is low.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…For low XG concentrations, the adsorption after rearrangement was faster than the adsorption onto uncovered CNC surfaces, indicating that XG chains adsorb on CNC in a rather flat conformation with a high percentage of trains in close contact with the cellulose surface. Conversely, for higher XG concentrations, the kinetic constant related to the conformational rearrangement decreases, indicating that XG molecules have no time to laterally rearrange before new XG molecules adsorb, and the XG loops and tails do not have time to laterally rearrange to a flat conformation before new XG molecules adsorb (Villares, Moreau et al 2015). In fact, the two CNC/XG complexes fabricated from low and high XG concentrations, respectively, show different enzymatic accessibility.…”
Section: Thin Films As Biomimetic Model and Biomass Degradation Modelmentioning
confidence: 98%
“…Sap transport and cavitation resistances are linked to nanoscale vessel architecture and the size of the torus present in the pits (Cochard 2006;Lens, Tixier et al 2013). Nanostructured surfaces of biopolymers thus provide simple, dense and anisotropic systems that can be used as tunable models of the interface and surface to mimic naturally-existing materials and investigate both fundamental hypotheses of plant cell wall biology such enzymatic degradation processes (Josefsson, Henriksson et al 2007;Ahola, Turon et al 2008;Cerclier, Guyomard-Lack et al 2013) or polymer interactions (Holmberg, Berg et al 1997;Stiernstedt, Nordgren et al 2006;Winter, Cerclier et al 2010;Villares, Moreau et al 2015). Nanostructured surfaces also serve to investigate complex industrial processes such as pulp production or paper coatings through a simplified approach.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation